2011
DOI: 10.1111/j.1365-3156.2011.02902.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and incidence of transfusion‐transmitted infectious diseases among blood donors from regional blood transfusion centres in Burkina Faso, West Africa

Abstract: Abstractbackground and objective The high prevalence of numerous transfusion-transmitted infectious diseases such as HIV, HBV, HCV and syphilis in sub-Saharan Africa affects blood safety for transfusion recipients. The aim of this study was to evaluate the prevalence and incidence of transfusiontransmissible infectious diseases among blood donors in Burkina Faso.methods A retrospective study of blood donors' records from January to December 2009 was conducted. Prevalence and incidence of viral infections were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
52
8
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 23 publications
13
52
8
4
Order By: Relevance
“…The study reported a low prevalence of HCV (0.9%, 2/217) among HBsAgpositive individuals. However, other studies have reported prevalence rates of 4.0% and 6.3% in Koudougou blood donors and regional blood transfusion centers of Burkina Faso, respectively (7,26). The prevalence rates ranging between 2.0% and 5.4% have been also reported among pregnant women in Ouagadougou (6,11,27,28).…”
Section: Discussionmentioning
confidence: 91%
“…The study reported a low prevalence of HCV (0.9%, 2/217) among HBsAgpositive individuals. However, other studies have reported prevalence rates of 4.0% and 6.3% in Koudougou blood donors and regional blood transfusion centers of Burkina Faso, respectively (7,26). The prevalence rates ranging between 2.0% and 5.4% have been also reported among pregnant women in Ouagadougou (6,11,27,28).…”
Section: Discussionmentioning
confidence: 91%
“…The overall seroprevalence for syphilis in this study is lower than 2.1% in Burkina Faso but higher than 0.1 to 0.5% in Ethiopia [2,17,18,41]. A prevalence of 0 to 8% has been reported for Nigeria [4,14,39,40].…”
Section: Discussionmentioning
confidence: 92%
“…The risk of transmitting HIV through blood transfusion in the developed country is 0.14 to 1.1 per million donations 1 . Report from Burkino Faso, a country in Africa gave a seroprevalence of 13.4% and 6.3% for HBV and HCV respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…In Another study in Burkina Faso, HBV was the most prevalent TTI (13.4%) of donors screened 15 . Other similar studies from other parts of sub-Saharan Africa have given similar high prevalence of HBV among blood donors for instance in South Sudan, 6.25% HBV prevalence was reported 16 .…”
mentioning
confidence: 99%